Umbilical hernia with uncommon content; herniated paraumbilical collateral veins - Taydaş, Onur; Oğul, Hayri; Kantarcı, Mecit (My University, 2025)
A 56-year-old man patient with umbilical hernia and abdominal pain was referred to our hospital for interventional and surgical treatment of hepatocellular carcinoma. The patient had a history of alcohol-related chronic liver disease. There was history of vomiting, nausea and weight loss over the past 3 months. On physical examination, the liver was detected by palpation in 5 cm below the costal margin. There was mild tenderness over his right hypochondriac region. During his physical examination, an umbilical hernia was noted. Biochemical analysis revealed an elevated level of liver enzymes [alanine aminotransferase (ALT) 77 IU/L (normal 19–33); aspartate aminotransferase (AST) 77 IU/L (normal 15–35)], moderate decreased level of serum albumin [albumin 26 g/L (normal 35–50)], and normal level of bilirubin.
Keywords: Umbilical Hernia; Enzymes; Hepatocellular Carcinoma; Collateral Vein